(untitled) (Journal of Naval Architecture and Marine Engineering, 2015)
In the present paper, the stiffening effect of carbon nanotubes is quantitatively investigated by micromechanics methods. The Mori-Tanaka effective-field method is employed to calculate the effective elastic moduli of composites with aligned or randomly oriented straight nanotubes. In addition, the epoxy resin is modified experimentally by adding SWCNT with different ratio i.e 0, 0.1, 0.3, 0.5 and 0.7 wt.-%. A comparison between the results for SWCNT/epoxy nanocomposite which obtained analytically and experimentally is done. In the experimental work the epoxy resin is modified by adding SWCNT with different ratio i.e 0, 0.1, 0.3, 0.5 and 0.7 wt.-%. The materials are characterized in tension to obtain the mechanical properties of SWCNT/epoxy nanocomposite experimentally. The results of micromechanics methods indicated that the CNTs are highly anisotropic, with Youngs modulus in the tube direction two orders of magnitude higher than that normal to the tube. The results shows a nanotube volume fraction of 0.3%of SWCNT improve all mechanical properties such as the tensile strength, modulus of elasticity and the toughness. Avoid the volume fraction greater than 0.5% SWCNT. The optimal value achieved experimentally, (at 0.3% SWCNT) lies between the analytical values (that achieved parallel to the CNT and the randomly orientated straight CNTs).